Safe ground water: I, contamination of ground water of Varanasi, Uttar Pradesh, India by nitrate, sulfates and alkalinity - Srivastav A.L.; Dubey V.K.; Singh P.K.; Sharma Y.C. (My University, 2025)
Nitrate is a problem in drinking water due to its harmful biological effects. High concentrations of nitrate are reported to cause methemoglobinemia, and have been established as a risk factor in developing gastric and intestinal cancer. Nitrate contamination of ground water has become a major challenge to the environmentalist, especially in the developing countries. The city of Varanasi withdraws a significant amount of drinking water from ground water sources. A large section of population in semi urban and rural areas of the district depends on ground water for drinking purpose. The present study was intended to identify the locations affected by nitrate contamination in ground water around Varanasi city. Both open wells (30 nos) and tube wells (15 nos) have been considered as sources supplying drinking water to the population. In addition to nitrates, the concentration of sulphates and alkalinity was specifically determined in the samples. Other quality parameters of concerns included in this study are pH, temperature, total dissolved solids (TDS), turbidity, chloride, dissolved oxygen (DO).